Internalizing Local Wisdom-Based Entrepreneurial Spirit in Islamic Elementary School - Muhamad Arif; Mohd Kasturi Nor bin Abd Aziz; Jesica Dwi Rahmayanti; Sulaiman Dorloh (Madrasah: Jurnal Pendidikan dan Pembelajaran Dasar, 2023)
The importance of implementing educational entrepreneurship from an early age is a new choice that must be driven by policymakers in the world of education, as was done at the SD Islam Muhammadiyah 1 Menganti Gresik, which provides a space for entrepreneurship learning for students based on local wisdom (chicken pieces). The purposes of this research are, first, how is the entrepreneurial spirit internalized in students based on local wisdom (chicken pieces)? Second, what are the obstacles that occur in the process of producing entrepreneurial spirit based on local wisdom in broiler students? The research method used is a qualitative case study approach. Primary data sources include class teachers, curriculum representatives, and students. Besides that, the analysis used by the researcher is condensation data, display, and conclusion drawing. The results of the study show that in the process of cultivating local wisdom-based entrepreneurial spirit in line with the educational entrepreneurship concept, "the element" includes talent and multiple intelligences, holistic education and passion, and regional excellence that develop in the surrounding community, as conveyed by Robinson and Aronica in their book The Element: How Finding Your Passion Changes Everything.